Sceny mysliwskie z Dolnego Slaska - Lozinski, Jozef, 1945- (Bydgoszcz : Pomorze, 1989)
A contemporary novel written with a cool eye toward present-day politics.
Keywords: Poland -- Politics and government -- 1980-1989 -- Fiction